DIAGNOSTIC ACCURACY OF ULTRASOUND AND LIVER FUNCTION TESTS FOR THE EARLY DETECTION OF COMMON BILE DUCT STONE (Journal of Medical & Health Sciences Review, 2025)
Introduction:Common bile duct stone (CBDS) is significantly challenging to predict via basic ultrasound impressions and LFTs; hence, making decisions and taking prompt action is difficult. The main goal of this study is to find out how useful ultrasound (US) and liver function tests (LFTs) are for finding common biliary duct stones.Materials and Methods:This retrospective observational study was conducted at the gastroenterology ward of Shifa International Hospital Islamabad. It includes data on 768 patients who underwent ultrasound and LFTs for the diagnosis of CBDS. After receiving consent, the investigator documented relevant patient demographics, ultrasound reports, and LFTs. Receiver operating characteristic curve (ROC) and area under the curve (AUC) analyses were used to compare the diagnostic performance of US and LFTs.Results:Compared to LFTs that included ALP, gGT, and SGOT, the sensitivities were 0.801, 0.913, and 0.849. The sensitivity reported for ultrasound impressions—CBD Diameter and CBD Obstruction—was 0.727 and 0.753, while the specificities were 0.587 and 0.819, respectively. ROC and AUC showed p-values < 0.05 (p = 0.0001), indicating highly significant outcomes. Each variable had a different AUC. The AUC for bile obstruction and CBD diameter (>7 mm) was 0.786 and 0.735. In contrast, gGT and ALP had AUCs of 0.953 and 0.897, respectively.Conclusion:Transabdominal ultrasound impressions are not as sensitive as LFTs in detecting choledocholithiasis, which involves the liver and bile ducts. The gGT test demonstrated the highest sensitivity in diagnosing CBDS